The qur'anic concept of Qiwamah: a review of commentaries on the Verse: 4:34 - Ahmad, Nadzrah; P, Muhammad Abdul Rasheed (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
This study elaborates the Qur´Énic verse ‘men are caretakers of women’ (4:34) which legitimizes the system of qiwÉmah (responsibility of man to protect and manage the affairs of woman). This is significant given the fact that the verse has been controversial since long, especially in the feminist discourses. The controversies are considerably intense often to the extent of remarking the verse and its commentaries misogynist. Employing a qualitative analysis method, the researcher has surveyed certain commentaries of both medieval and modern times, comparing them with modern Muslim scholarly interpretations of the verse. As a result, the study reveals that a blanket assertion meant to characterize the commentaries on the verse of qiwÉmah as a tool of male oppression is untenable. It also finds that qiwÉmah, according to the commentaries, is a theoretical foundation meant to preserve two key realms of the Qur´Énic paradigm. Firstly, to maintain a peaceful system of family with fully complementary gender roles and secondly, the protection of woman.